Evaluation of an innovative hands‐on anatomy‐centered ultrasound curriculum to supplement graduate gross anatomy education. Issue 4 (21st November 2016) - Royer, Danielle F.; Kessler, Ross; Stowell, Jeffrey R.
Abstract : Ultrasound (US) can enhance anatomy education, yet is incorporated into few non‐medical anatomy programs. This study is the first to evaluate the impact of US training in gross anatomy for non‐medical students in the United States. All 32 master's students enrolled in gross anatomy with the anatomy‐centered ultrasound (ACUS) curriculum were recruited. Mean Likert ratings on pre‐ and post‐course surveys (100% response rates) were compared to evaluate the effectiveness of the ACUS curriculum in developing US confidence, and gauge its impact on views of US. Post‐course, students reported significantly higher ( P < 0.001) mean confidence ratings in five US skills (pre‐course versus post‐course mean): obtaining scans (3.13 ±1.04 versus 4.03 ±0.78), optimizing images (2.78 ±1.07 versus 3.75 ±0.92), recognizing artifacts (2.94 ±0.95 versus 3.97 ±0.69), distinguishing tissue types (2.88 ±0.98 versus 4.09 ±0.69), and identifying structures (2.97 ±0.86 versus 4.03 ±0.59), demonstrating the success of the ACUS curriculum in students with limited prior experience. Views on the value of US to anatomy education and to students' future careers remained positive after the course. End‐of‐semester quiz performance (91% response rate) provided data on educational outcomes. The average score was 79%, with a 90% average on questions about distinguishing tissues/artifacts, demonstrating positive learning outcomes and retention. The anatomy‐centered ultrasound curriculum significantly increased confidence with and knowledge of US among non‐medical anatomy students with limited prior training. Non‐medical students greatly value the contributions that US makes to anatomy education and to their future careers. It is feasible to enhance anatomy education outside of medical training by incorporating US. Anat Sci Educ 10: 348–362. © 2016 American Association of Anatomists.